Science and mathematics Advanced Placement exams: Growth and achievement over time - Judson, Eugene (The Journal of educational research (Washington, D.C.), 2017)
Rapid growth of Advanced Placement (AP) exams in the last 2 decades has been paralleled by national enthusiasm to promote availability and rigor of science, technology, engineering, and mathematics (STEM). Trends were examined in STEM AP to evaluate and compare growth and achievement. Analysis included individual STEM subjects and disaggregation by ethnicity. Analysis indicates growth in STEM AP was extraordinary but was slightly outmatched by non-AP subjects. Moreover, growth in STEM AP has been most pronounced among underrepresented minorities, even though their achievement has slightly declined. Interestingly, the proportion of students scoring at the lowest level grew steadily for all students from 1997 to 2010, yet this proportion was substantially less for Asian and White students compared to underrepresented minorities. Finally, it was found that achievement in most high-participation STEM subjects slightly decreased from 1998 to 2013, while achievement held steady or slightly increased in lower participation STEM AP subjects.